Esophagectomy in octogenarians: is it at a cost?. Issue 12 (December 2022) - Ojha, Sujata; Darwish, Muhammad B.; Benzie, Annie L.; Logarajah, Shankar; McLaren, Patrick J.; Osman, Houssam; Cho, Edward; Jay, John; Jeyarajah, D. Rohan
Abstract: Background: Surgical intervention in the geriatric population has a higher risk of perioperative morbidity and mortality due to frailty, comorbidities, and lack of compensatory physiologic reserve. The literature on esophagectomy in octogenarians is limited and there is concern about elderly patients being with-held surgery. The purpose of this study is to analyze the outcomes of esophagectomies for esophageal cancer in octogenarians to assess the safety of esophagectomy in this population. Methods: 145 transhiatal esophagectomies performed for esophageal cancer between 2012 and 2020 were retrospectively reviewed in this IRB approved study. Two aborted esophagectomies were excluded. Patient demographics, surgical outcomes, and oncologic outcomes were reviewed. The octogenarian group was analyzed compared to patients younger than 80 years of age. Results: Among 143 esophagectomies, 136 patients were <80 years old while 7 were ≥80 years old. Octogenarians received significantly less neoadjuvant therapy compared to younger patients (42.9% vs 80.2%, p = 0.02). No statistically significant difference was noted in complication rate, length of stay (LOS), estimated blood loss (EBL), or mortality. However, octogenarians were found to have an increase in severity of complications compared to younger patients. Conclusion: This study demonstrates that esophagectomy can be performed in carefully selected octogenarians. This comes at a cost with increased severity of complications without an increase in complication rates or mortality. This data suggests that esophagectomy can be offered selectively to older patients with clear expectations and planning for the high risk of more severe post-operative complications. Abstract : Esophagectomy; Octogenarians; Geriatric surgery; Esophageal cancer.